Estudio Diferenciado Por Edad Y Nivel Cultural Sobre Las Disfunciones Sexuales En Las Pacientes En Climaterio Que Acuden Al “Club De Vitalidad” De La Ciudad De Guayaquil. - PALACIOS TÁVARA, MARIA DEL SOCORRO (2014)
This Thesis has been performed as Research Report presented as a prerequisite to obtain the title of Master in Health Services Management. Study differentiated by age and educational level on sexual dysfunctions in patients attending the climacteric "Club of vitality" of the city of Guayaquil. The Club of Vitality, to perform research study of this work, I have encountered several problems, including: that the impact of sexual health varies according to the age of the patient, who do not receive individualized care specialists understood on the topic of sexuality, there is no additional organized and planned in the Club of vitality attention, so often given lectures do not cover issues related to menopause and its affectations and patients often take a long time to be registered and do not even get all the benefits of the club. After applying the research methodology with its non-experimental design and the application of techniques and instruments of research we conclude that the application of treatment protocols to graze a multidisciplinary team care related climacteric and program advice and guidance on all changes in the short, medium and long term aimed at preventing patients seeking involvement in their quality of life in addition to that individualized therapies for patients who will receive the same friendly treatment in less time and getting all club benefits such as therapies, seeking help specialists who provide therapies to improve their quality of life, a better relationship with their environment will be promoted.